Peran Guru PKN dalam Membentuk Generasi Unggul Berkarakter Pancasila - Sunaryati, Titin; Rosdiana, Nazwa; Agustin, Helen Bela; Keswani, Anjeni Fatiha Galuh; Rahmawati, Novi (Universitas Pahlawan Tuanku Tambusai, 2024)
Developing national character through character education in schools is a mission aligned with the vision for the Indonesian nation. The goal of democratic and high-quality national education is to cultivate individuals with strong moral character, creativity, innovation, a sense of national pride, intelligence, health, discipline, responsibility, skills, and a good grasp of science and technology. Despite these goals, studies and interviews reveal that juvenile delinquency, often exceeding acceptable boundaries, still persists. Limited supervision contributes to problems such as school violence, further aggravated by a lack of family involvement. This study seeks to assess the impact of Pancasila and Citizenship Education in shaping student character, drawing on interviews with teachers and students, as well as school observations.